Thrombin generation and secretion of platelet Factor 4 during blood clotting. - Shuman, M A (1978)
We have studied the platelet release reaction and thrombin generation during the spontaneous clotting of whole blood in vitro. Both thrombin formation and secretion of platelet Factor 4 were detected at least 12 min before clotting (clotting time, 22--26 min). Initially, at low thrombin concentrations (2--5 ng/ml), there is a small increase in plasma platelet Factor 4 (less than 1% of the amount present in serum). This is followed by a gradual increase in both platelet Factor 4 and thrombin concentrations over a 12 to 20-min interval. Finally, 5 min 5 before clotting, there is a rapid increase in both thrombin generation and platelet secretion. Thus, we have shown that the release of platelet Factor 4 is a prolonged reactoin and the extent to which it occurs parallel thrombin generation. It is only when thrombin concentrations are high (45--90) ng/ml)--during the period of clot formation--that the major part of platelet Factor 4 secretion occurs. Release of platelet Factor 4, like fibrin formation, occurs in the last step of in vitro coagulation.